Analgesic and Antibacterial Activity of Methanolic Extract of Smilax lanceifolia Nepal - Prajapati, Juli (International Journal of Pharmaceutical & Biological Archive, 2014)
Analgesic and Antibacterial Activity of Methanolic Extract of Smilax lanceifolia Nepal